Microelimination of Chronic Hepatitis C by Universal Screening Plus Direct-Acting Antivirals for Incarcerated Persons in Taiwan. (17th July 2020) - Yang, Tsung-Hua; Fang, Yu-Jen; Hsu, Shih-Jer; Lee, Ji-Yuh; Chiu, Min-Chin; Yu, Jian-Jyun; Kuo, Chia-Chi; Chen, Chien-Hung
Abstract: Background: Incarcerated persons are a special population with higher hepatitis C virus (HCV) prevalence and should be prioritized for microelimination. In this study, we investigate the seroprevalence and evaluate the effectiveness and safety of direct-acting antiviral (DAA) therapy in custodial settings. Methods: Incarcerated persons in Yunlin Prison were recruited to receive anti-HCV antibody screening. Patients with positive HCV ribonucleic acid (RNA) were treated with glecaprevir/pibrentasvir (GLE/PIB) in our special chronic hepatitis C (CHC) clinic in prison. The primary endpoint was sustained virologic response at week 12 off therapy (SVR12). Results: A total of 1402 incarcerated persons were invited to anti-HCV screening and 824 (58.7%) accepted. The prevalence of anti-HCV positivity was 33.5% (276 of 824), and the viremic rate (detectable HCV RNA) was 69.2% (191 of 276). According to fibrosis index based on 4 factors, patients with F3 stage were 6 (3.1%), but none met the criteria of F4 stage. However, 6 (3.1%) had liver cirrhosis with splenomegaly, confirmed by findings of ultrasonography. The median log10 HCV RNA level at baseline was 6.235 (2.394–7.403). Genotype (GT) 6 was predominant (39.3%), followed by GT 1a (22.0%) and 1b (14.1%). Mixed GT HCV infection accounted for 3.6% of total infections. In total, 165 patients received GLE/PIB therapy. The overall SVR12 rates were 100%. Conclusions: Direct-acting antiviral therapy is highly effective and safe for incarcerated patients in Taiwan. Our special prison-based CHC clinic, linking universal screening to medical care, can serve as a model for microelimination of HCV in custodial settings. Abstract : We established a special hepatitis C clinic in prison and offered universal hepatitis C screening for incarcerated persons. The prevalence of anti-HCV positivity was 33.5%, and the viremic rate (detectable HCV RNA) was 69.2%. All treated patients achieved SVR.